The Effect of Web-Based Game Media (Earthgames) on Critical Thinking Skills in Earth Structure Learning for Junior High School Students - Lewi Damar Oktavian; Eka Budhi Santosa; Fatma Sukmawati; Cinta Kasih Putri Thomas (Universitas Sebelas Maret, 2026)
This study investigates the effect of web-based game media, specifically Earthgames supported by the Wordwall platform, on the critical thinking skills of eighth-grade students in the topic of Earth Structure in the Natural Sciences (IPA) subject. A pre-experimental design using a one- group pretest-posttest approach was employed, involving 64 students from SMP Negeri 27 Surakarta during the 2025/2026 academic year. Data were collected through validated critical thinking tests covering indicators of interpretation, analysis, evaluation, inference, explanation, and problem-solving based on Facione's framework. Results showed a significant improvement in students' mean scores from 45.57 (pretest) to 67.27 (posttest). The hypothesis test using the Paired Sample t-test (Sig. < 0.001) confirmed a statistically significant difference, with an N- Gain score of 0.43 (moderate category). These findings indicate that Earthgames via Wordwall positively influenced students' critical thinking by providing interactive, visual, and game-based learning experiences. The media supports Mayer's Cognitive Theory of Multimedia Learning and aligns with the constructivist principles underpinning 21st-century science education.